Bispecific antibody targeting TGF-β and PD-L1 for synergistic cancer immunotherapy - Li, Tianye; Wang, Xinrun; Niu, Mengke; Wang, Mingli; Zhou, Jianwei; Wu, Kongming; Yi, Ming (Frontiers in Immunology, 2023)
The PD-1/PD-L1 signaling pathway plays a crucial role in cancer immune evasion, and the use of anti-PD-1/PD-L1 antibodies represents a significant milestone in cancer immunotherapy. However, the low response rate observed in unselected patients and the development of therapeutic resistance remain major obstacles to their clinical application. Accumulating studies showed that overexpressed TGF-β is another immunosuppressive factor apart from traditional immune checkpoints.Actually, the effects of PD-1 and TGF-β pathways are independent and interactive, which work together contributing to the immune evasion of cancer cell. It has been verified that blocking TGF-β and PD-L1 simultaneously could enhance the efficacy of PD-L1 monoclonal antibody and overcome its treatment resistance. Based on the bispecific antibody or fusion protein technology, multiple bispecific and bifunctional antibodies have been developed. In the preclinical and clinical studies, these updated antibodies exhibited potent anti-tumor activity, superior to anti-PD-1/PD-L1 monotherapies. In the review, we summarized the advances of bispecific antibodies targeting TGF-β and PD-L1 in cancer immunotherapy. We believe these nextgeneration immune checkpoint inhibitors would substantially alter the cancer treatment paradigm, especially in anti-PD-1/PD-L1-resistant patients.